2004
DOI: 10.1063/1.1667011
|View full text |Cite
|
Sign up to set email alerts
|

Single virus particle mass detection using microresonators with nanoscale thickness

Abstract: In this letter, we present the microfabrication and application of arrays of silicon cantilever beams as microresonator sensors with nanoscale thickness to detect the mass of individual virus particles. The dimensions of the fabricated cantilever beams were in the range of 4–5 μm in length, 1–2 μm in width and 20–30 nm in thickness. The virus particles we used in the study were vaccinia virus, which is a member of the Poxviridae family and forms the basis of the smallpox vaccine. The frequency spectra of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
323
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 520 publications
(328 citation statements)
references
References 8 publications
2
323
0
3
Order By: Relevance
“…Антитела к гепати там А и С были иммобилизованы на разных кан тилеверах, предел обнаружения составил 0,1 нг/мл (1,6 пМ). Гупта в работе [21] показал, что чувстви тельности кантилевера по измерению массы доста точно, чтобы взвесить отдельный вирус коровьей оспы, однако он не использовал специфичного сен сорного слоя.…”
Section: Eexamples Of Biosensors Based On Microcantilevers For Detectunclassified
See 1 more Smart Citation
“…Антитела к гепати там А и С были иммобилизованы на разных кан тилеверах, предел обнаружения составил 0,1 нг/мл (1,6 пМ). Гупта в работе [21] показал, что чувстви тельности кантилевера по измерению массы доста точно, чтобы взвесить отдельный вирус коровьей оспы, однако он не использовал специфичного сен сорного слоя.…”
Section: Eexamples Of Biosensors Based On Microcantilevers For Detectunclassified
“…Antibodies to hepatitis A and C were immobilized on differ ent cantilevers, the detection limit was 0.1 ng/ml (1.6 pmole). Gupta in [21] showed that the sensitivity of the cantilever to measure the mass is enough to weigh single vaccinia virus, but he did not use a specific sensor layer.…”
Section: Eexamples Of Biosensors Based On Microcantilevers For Detectmentioning
confidence: 99%
“…The adsorption of gold atoms onto a nanoscale silicon carbide (SiC) clamped-clamped beam has been detected successfully through resonant frequency-shift [2]. Other studies have demonstrated the resonant detection of single-stranded DNA (ssDNA) probes [3] and Vaccinia virus particles [4] immobilised on microstructures. The detection of various biological elements is 10 a widely researched area of resonant mass sensing with functionalised surfaces promoting the attachment of the target analytes.…”
Section: Introductionmentioning
confidence: 99%
“…With precise optical detection of atomic force microscopy (AFM), a single cell or virus has been sensed in air environment [8,9]. In ultrahigh vacuum, the resonant cantilevers even showed the mass resolution as high as attogram level [10].…”
Section: Introductionmentioning
confidence: 99%
“…Differently, the dynamic detecting method employs the cantilever as a resonator. Induced by specific mass adsorbate, a shift in the resonant frequency is read out as the sensing signal [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%